Pengaruh Fasilitas Perpustakaan terhadap Minat Baca Buku Mata Pelajaran Ekonomi Jurusan IPS - Waladow, Mirman; Bumulo, Frahmawati; Bahsoan, Agil; Hafid, Radia; Mahmud, Melizubaida (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the effect of library facilities on students' interest in reading books in economics for grades 10, 11, and 12, majoring in social studies at SMA Negeri 1 Kabila, Bone Bolango Regency, Gorontalo Province. This study used a quantitative approach. Data collection methods used in this study were observation, documentation, and questionnaires. Based on the description above, the population in this study was 489 students in grades 10, 11, and 12 majoring in social studies at SMA Negeri 1 Kabila. The sample in this study was grades 10, 11, and 12. The analytical method used was simple linear regression. The results showed an effect. The results obtained a R-squared coefficient of 0.258. This value means that 25.8% of the variability in the variable of interest in reading economics textbooks for grades 10, 11, and 12 majoring in social studies at SMA Negeri 1 Kabila, Bone Bolango Regency, Gorontalo Province can be explained by library facilities, while the remaining 74.2% is influenced by other variables not examined in this study.